The Method Of Reading In Arabic Teaching Based On The Psychological Linguistic/ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ù†Ø§Ø¡ Ø¹Ù„Ù‰ Ù†Ø¸Ø±Ø© Ø¹Ù„Ù… Ø§Ù„Ù†ÙØ³ Ø§Ù„Ù„ØºÙˆÙŠ - Umam, Muh Hotibul (Ijaz Arabi Journal of Arabic Learning, 2021)
This study discusses reading methods in Arabic learning which are based on psycholinguistics. This study is motivated by the existing of teachers who have difficulties in choosing appropriate method for foreign beginners in learning Arabic, and accordance with the study of psycholinguistics. Therefore, this study aims to find out learning methods that are built from the study of psychology, and make a teacher easier to compile material that is suitable in accordance with the conditions and students’ thought level, as well as provide an overview in making methods that are suitable for all levels of students. The method used to apply this research is literature study in the form of documentations such as Arabic books and Indonesian language literature, as well as conducting in depth analysis in a inductive way so that obtain independent information. The results of this study are reading methods in Arabic learning consists of 3 things: First, basic understanding related to the reading method. Second, reading method in Arabic language learning has advantages because of its purpose, with handbooks prepared as reading material, and additional books to expand knowledge (information), and with its foundation that becomes the basis. Third, the teacher’s steps in applying reading method. The theory of psychological science in reading method consists of 7 things. First, the understanding of reading. Second, the opinion of expert related to the reading. Third, the patterns of reading in psychology. Fourth, the way of interact with books. Fifth, the strategy of reading. Sixth, text and reader. Seventh, the role of reading in producing an article.